Php 5 Unleashed - John Coggeshall (Pearson, 2005)
Over 12 million Internet domains worldwide use the PHP language to power their websites. If you are a programmer included in this group, or would like to be one, you should pick up a copy of PHP Unleashed. The definitive guide in PHP programming, PHP Unleashed thoroughly and authoritatively covers the release of PHP 5, as well as advanced topics not found in other books. It begins with a detailed summary of the basics and then quickly moves on to more advanced topics such as working with data, outputting graphical data and building complete applications. Whether you're an experienced programmer and new to PHP, or an experienced PHP programmer but new to PHP 5, this is the one PHP book you need in your library.